The assessment of acceptance and identification of barriers to use of electronic medical records by doctors in emergency centres in Cape Town, South Africa - Chagani, Mohamedsuhel (Stellenbosch : Stellenbosch University, 2017)
Thesis (MFamMed)--Stellenbosch University, 2017.